Heart rate variability and inflammation: a meta-analysis of human studies - Williams, DeWayne P.; Koenig, Julian (Brain, behavior and immunity, 2019)
The inflammatory reflex is known as the body’s primary defense against infection and has been implicated in a number of diseases. The magnitude of the inflammatory response is important, as an extreme or insufficient response can be differentially harmful to the individual. Converging evidence suggests that the autonomic nervous system (ANS) regulates the inflammatory reflex. Heart rate variability (HRV) can be separated into components that primarily reflect parasympathetic (PNS) or vagal activity (i.e., indices of vagally mediated HRV) and a combination of both sympathetic (SNS) and PNS influences. Given the physiological relation between the vagus and inflammatory processes, one would expect to find higher HRV, especially indices of vagally-mediated HRV, to be associated with decreased levels of inflammation via the cholinergic anti-inflammatory pathway. However, existing findings here are mixed, such that studies have also shown a positive association between indices of HRV and markers of inflammation. Therefore, the present meta-analysis aimed to synthesize existing studies, estimating the general direction and strength of the relationship between different indices of HRV and inflammatory markers. A systematic search of the literature yielded 2283 studies that were screened for inclusion eligibility (159 studies eligible for inclusion); in sum, 51 studies reported/provided adequate information for inclusion in meta-analyses. Results generally showed negative associations between indices of HRV and markers of inflammation. In this regard, the standard deviation of R-R intervals (SDNN) and power in the high frequency band of HRV (HF-HRV) showed the strongest and most robust associations with inflammatory markers compared to other time- and frequency-domain measures of HRV. Overall, we propose that indices of HRV can be used to index activity of the neurophysiological pathway responsible for adaptively regulating inflammatory processes in humans.
Gesehen am 18.09.2019